ANAMIUALITY OF IMMUNOLOGICAL MARKERS IN THE EARLY RECONSTRUCTION OF GYNECOLOGICAL COMPLICATIONS IN AUOLS WITH LEUOMYOMAS IN RERRODUCTIVE AGE - Haydarova, N.V.; Narzullaeva , N.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction: In this study, the dynamics of biomarkers characterizing the activation of the humoral immune response and destructive pathologies in patients with prostate leiomyoma were analyzed. According to the established data, patients showed an increase in the number of metabolic immunocomplexes and a high concentration of IgA immunoglobulin. This indicates the active participation of immunological mechanisms in the pathogenesis of leiomyoma, in particular, the humoral immune system.Materials and methods. During our study, 36 patients with uterine leiomyoma were examined in the gynecological department of the Bukhara City Maternity Complex. The average age of the examined women was 50.1±4.09 years. In 64.0% of patients, ultrasound revealed one myomatous node, and in 36.0% of patients - several nodes. The total volume of the uterus in 58.0% of patients was at 4-5 weeks of pregnancy, in 42.0% - at 6-9 weeks. Patients did not have complaints characteristic of leiomyoma (57.0%); 27.0% had painful periods, and 16.0% had severe and prolonged periods. The results of the study showed that the level of IgA in the blood serum of women in the control group averaged 1.85±0.12 g/l, which is between the upper and upper limits of the norm - 1.46 and 2.22 g/l. The level of IgA in blood serum in women diagnosed with uterine leiomyoma was comparable to the control group.